May or Might? Strength, Duality and Social Meaning - Karawani, Hadil; Waldon, Brandon (Proceedings of the Amsterdam Colloquium, 2025)
This paper addresses one longstanding claim about epistemic must, namely that its semantic dual is the modal auxiliary might. While this is a “usual assumption” in the natural language semantics literature (Lassiter 2016: 14), it is not universally accepted: Crespo, Karawani, and Veltman (2017) (henceforth CKV) propose a theory of epistemic modality whereby the dual of must is may, the non-subjunctive counterpart of might. According to their view, an assymetric entailment relation holds between may and might, whereby might is weaker than may with respect to speakers’ expectations about the likelihood of the prejacent. Consistent with this view, the results of one experiment suggest that English speakers consider may p to be stronger than might p on two metrics: perceived speaker certainty of p and inferred likelihood of p. In two subsequent experiments, we were unable to find conclusive evidence that speakers distinguish between epistemic may and might in discourse contexts, including in epistemic contradiction contexts of the form must p, but might/may not p. We interpret this as evidence that the “usual assumption” at a minimum needs to be revised to accommodate may. We conclude with a discussion of the diachronic, cross-linguistic, and social meaning facets of epistemic modality that are uniquely accounted for by the framework of CKV.